Does handball throwing velocity increase after an eccentric overload-induced postactivation potentiation? - Asencio, P.; Sabido, R.; García-Valverde, A.; Hernández-Davó, J. L. (European Journal of Human Movement, 2020)
Introduction: Post-activation performance enhancement (PAPE) has been defined as an increase in performance of voluntary movements after a high-intensity voluntary task. This phenomenon can be achieved through different strategies. However, the relationship between a conditioning eccentric overload (EO) exercise and PAPE in the upper extremities is scarce. The aim of this work was to study the application of PAPE to improve handball throwing velocity using EO, and to compare it with a traditional resistance training exercise. Material and methods: Fourteen team handball players carried out two sessions with different PAPE protocols. One of the sessions consisted of performing a PAPE protocol through a set of three repetitions at 90% of RM in the bench press (BP). In the other session, a set of three maximal-effort repetitions of one-handed horizontal press was carried out using a conical pulley (CP) with a 0.16 kg•m2 inertial load. Throwing velocity was measured pre and post both protocols. Results: Both protocols showed a non-significant handball throwing velocity after the application of PAPE protocols (effect size = 0.24 and 0.20 for CP and BP respectively). Conclusions: None of the procedures obtained the expected PAPE phenomenon for the improvement of handball throw velocity. Future studies need to assess different EO protocols to elicit PAPE in complex sport-related actions.